Recent Technology-Aided Programs to Support Adaptive Responses, Functional Activities, and Leisure and Communication in People With Significant Disabilities - Lancioni, Giulio E.; Olivetti Belardinelli, Marta; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria (Frontiers in Neurology, 2019)
This paper presents an overview of recent technology-aided programs (i.e., technology-aided support tools) designed to help people with significant disabilities (a) engage in adaptive responses, functional activities, and leisure and communication, and thus (b) interact with their physical and social environment and improve their performance/achievement. In order to illustrate the support tools, the paper provides an overview of recent studies aimed at developing and assessing those tools. The paper also examines the tools’ accessibility and usability, and comments on possible ways of modifying and advancing them to improve their impact. The tools taken into consideration concern, among others, (a) microswitches linked to computer systems, and aimed at promoting (i.e., through positive stimulation) minimal responses or functional body movements in individuals with intellectual disabilities and motor impairments; (b) computer systems, tablets, or smartphones aimed at supporting functional activity engagement of individuals with intellectual disabilities or Alzheimer’s disease; and (c) microswitches with computer-aided systems, elaborate communication devices, and specifically arranged smartphones or tablets, directed at promoting leisure, communication, or both.